• Решите уравнение :
    3. (6х-1)^2-(3-8x)(3+8x)=(10x+1)^2.
    4. 5(x+2)^2+(2x-1)^2-9(x+3)(x-3)=22.

Ответы 1

  • (6х-1)^2-(3-8x)(3+8x)=(10x+1)^2.(6x-1)²-(3-8x)(3+8x)-(10x+1)²=0(6x-1)²+(8x-3)(8x+3)-(10x+1)²=0(36x²-12x+1)+(8x-3)(8x+3)-(100x²+20x+1)=0(36x²-12x+1)+(64x²-9)-(100x²+20x+1)=036x²-12x+1+64x²-9-100x²-20x-1=0-32x-9=0-32x=932x=-9x=(-9)÷32x=-9/325(x+2)^2+(2x-1)^2-9(x+3)(x-3)=225(x+2)²+(2x-1)²-9(x+3)(x-3)-22=05(x²+4x+4)+(4x²-4x+1)-9(x+3)(x-3)-22=0(5x²+20x+20)+(4x²-4x+1)-(9x+1)-(9x+27)(x-3)-22=0(5x²+20x+20)+(4x²-4x+1)-(9x²-27x+27x-81)-22=0(5x²+20x+20)+(4x²-4x+1)-(9x²-81)-22=05x²+20x+20+4x²-4x+1-9x²+81-22=016x+80=016x=-80x=(-80)÷16x=-5
    • Автор:

      skeeter
    • 4 года назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years